Enhancing Physics Knowledge for Teaching – Current, Electricity - Atarah, Samuel (The University of Hull)
In this session we will be introducing electric currents. We will consider how an electric current behaves in DC and AC circuits, and how these circuits are described with circuit components like resistors, capacitors and inductors.